2021
DOI: 10.22376/ijpbs/lpr.2021.11.2.l131-134
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Potential Extracellular Cellulase Producer and Determination of Cellulase Production Efficiency with Various Raw Substrates

Abstract: Cellulase is one of the important groups of enzyme for many industrial applications. It is applied in various processes of food industries, paper and pulp industry, fabric industry, medicine and pharma industry, agriculture industries etc. Microorganisms are among the most potential source for large scale production of this enzyme. The current study is aimed to isolate microorganisms which are capable of producing cellulase and to determine its efficiency for production of cellulase with different raw material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…26 Similar to this, many other studies have also used this technique for easy and fast screening of potential isolates. [28][29][30] Obtained results for zone of clearance are mentioned in the table below 2 and Figure 1 & 2. Based on the results of zone of clearance, it was found that, out of total 24 isolates, 15 were found to produce exocellulase.…”
Section: Resultsmentioning
confidence: 99%
“…26 Similar to this, many other studies have also used this technique for easy and fast screening of potential isolates. [28][29][30] Obtained results for zone of clearance are mentioned in the table below 2 and Figure 1 & 2. Based on the results of zone of clearance, it was found that, out of total 24 isolates, 15 were found to produce exocellulase.…”
Section: Resultsmentioning
confidence: 99%
“…For example, another study found that inoculation of alfalfa silage with lactic acid bacteria preparations increased the CP content and effectively reduced Bacillus Escherichia coli populations [41]. Cellulases, mainly consisting of endo-β-glucanase, exo-β-glucanase, and β-glucosidase, are capable of disrupting the cellulose crystal structure at the nonreducing end of the fiber molecule and releasing simple sugars [42]. The NDF and ADF contents are key indicators to evaluate the quality of silage: when the NDF and ADF contents are approximately low, the silage forage value is approximately high.…”
Section: Effect Of Moisture Content and Additives On Chemical Composi...mentioning
confidence: 99%